Study the Characteristics of TiO2: Ag Pure and Doped Films as Gas Sensor (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research, thin films of titanium dioxide were prepared and doped with certain doping percentages (2, 4, 6)% of silver. The films were prepared at a temperature of (400°C) and deposited on glass floors using thermal chemical spraying technique, after which it was annealed. At a temperature of (300Cº) for two hours, the results of the X-ray examination showed that the prepared pure and silver-dotted titanium dioxide films possess a polycrystalline structure of the Anatase type, and we note an increase in the growth of crystalline levels and their intensity with the increase in the percentage of doping. The results of the optical properties showed that the doping led to a decrease in transmittance and energy gap and an increase in absorbance, while the results of the Hall effect showed a clear increase in the concentration of carriers and a decrease in mobility values ​​at room temperature with an increase in doping ratios. The results of gas sensitization to nitrogen dioxide showed that the sensitivity increases with increasing doping, where the best sensitivity appeared at (6%) of doping at a temperature of (200Cº).